Shallow Sea Gas Manifestations in the Aegean Sea (Greece) as Natural Analogs to Study Ocean Acidification: First Catalog and Geochemical Characterization - Daskalopoulou, Kyriaki; D’Alessandro, Walter; Longo, Manfredi; Pecoraino, Giovannella; Calabrese, Sergio (Frontiers in Marine Science, 2022)
The concepts of CO2 emission, global warming, climate change, and their environmental impacts are of utmost importance for the understanding and protection of the ecosystems. Among the natural sources of gases into the atmosphere, the contribution of geogenic sources plays a crucial role. However, while subaerial emissions are widely studied, submarine outgassing is not yet well understood. In this study, we review and catalog 122 literature and unpublished data of submarine emissions distributed in ten coastal areas of the Aegean Sea. This catalog includes descriptions of the degassing vents through in situ observations, their chemical and isotopic compositions, and flux estimations. Temperatures and pH data of surface seawaters in four areas affected by submarine degassing are also presented. This overview provides useful information to researchers studying the impact of enhanced seawater CO2 concentrations related either to increasing CO2 levels in the atmosphere or leaking carbon capture and storage systems.